A systematic review of neuropsychological studies involving young binge drinkers. (July 2018) - Carbia, Carina; López-Caneda, Eduardo; Corral, Montserrat; Cadaveira, Fernando
Highlights: Binge drinking (BD) is associated with verbal memory and executive deficits (principally inhibition). Potential deficits in prospective memory and decision-making require further study. Attention, speed, short-term memory and visuospatial construction seem unaffected. Female BDs does not seem to show greater vulnerability than male BDs. Recovery deficits and the cumulative effects of BD have scarcely been explored. Abstract: Binge drinking (BD) is a public health concern with serious implications for brain development. This review is the first in which neuropsychological studies of healthy young BDs are synthesized following PRISMA guidelines. We conducted a literature search in PsycINFO, Web of Science, and PubMed. Articles were screened using strict inclusion criteria. Two authors independently assessed the methodological quality. Of the 27 studies included, 14 (52%) were of intermediate quality, 7 (26%) of poor quality and 6 (22%) of high quality. BD is associated with deficits in verbal memory and executive functions, principally poor inhibitory control. Tentatively, BD may be related to deficits in cognitive flexibility and monitoring of information in working memory. Further studies are needed to determine potential impairments in prospective memory and decision-making. BDs do not seem to show difficulties in planning, short-term memory, attention, processing speed or visuospatial construction. The evidence does not seem to support greater vulnerability in females. Future longitudinal studies should identify the characteristics of extreme trajectories, explore recovery deficits and design intervention programs.